Using explicit knowledge models and best practice guidelines to improve humanitarian outcomes through the development of a knowledge tool for international health workers - Overlack, David John (Curtin University, 2016)
This study attempts to improve Red Cross health workers’ access and use of information to improve decision making processes through understanding the deficiencies and limitations that currently exist within the Red Cross movement around knowledge management. The development of mobile computing and communication devices is transforming how aid organisations collect, use and transform data into actionable knowledge. A portable reference resource has been developed for humanitarian health workers along with a proposed modified decision-making framework.